Environmentalities of Coexistence with Wolves in the Cantabrian Mountains of Spain - Marino, Agnese; Blanco, JuanCarlos; Cortes-Vazquez, JoseA; López-Bao, JoséVicente; Bosch, AnnaPlanella; Durant, SarahM (Medknow, 2022)
Coexistence between humans and large carnivores is mediated by diverse values and interactions. We focus on four sites in the Cantabrian Mountains of Spain with a history of continuous wolf presence to examine how perceptions of coexistence vary across contexts. We conducted semi-structured and informal interviews with livestock farmers (n = 271), hunters (n = 157), and local community members (n = 60) to collect quantitative and qualitative data on people's experiences of coexistence with wolves. We use an environmentality framework to analyse approaches to wolf governance across sites and explore how local resource users perceive, negotiate, and respond to different governance approaches. Our analysis is firstly structured around coexistence subjectivities associated with pastoralist and hunter cultures. These encompass ambivalent and multi-layered relations founded on notions of reciprocity with nature and on resource users' roles as producers and land stewards. Secondly, we explore encounters between local cultures, interests, and environmental regulations in the context of different site-based environmentalities. The framework we adopt enables coexistence to be conceived as a space of competing knowledges and practices, arising from everyday embodied interactions with wolves and the cultural politics through which local communities negotiate different ways of governing, knowing, and relating to nature.